Does Female Reservation affect Long-Term Political Outcomes? Evidence from Rural India - Deininger, Klaus; Jin, Songqing; Nagarajan, Hari K.; Xia, Fang (Taylor and Francis, 2014)
While studies have explored the impacts of political quotas for females at household level, differential effects on males and females and their evolution through time have received little attention. Using nationwide data from India spanning a 15-year period, we find that, while leader quality declines, gender quotas increase the level and quality of women’s political participation, their ability to hold leaders to account, and their willingness to contribute to public goods. Key effects persist beyond the reserved period and impacts on females often materialize only with a lag.